2014
DOI: 10.1007/s00429-014-0793-x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Electrode Recording Tool for EXtracellular potentials (VERTEX): comparing multi-electrode recordings from simulated and biological mammalian cortical tissue

Abstract: Local field potentials (LFPs) sampled with extracellular electrodes are frequently used as a measure of population neuronal activity. However, relating such measurements to underlying neuronal behaviour and connectivity is non-trivial. To help study this link, we developed the Virtual Electrode Recording Tool for EXtracellular potentials (VERTEX). We first identified a reduced neuron model that retained the spatial and frequency filtering characteristics of extracellular potentials from neocortical neurons. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 85 publications
(180 reference statements)
0
56
0
Order By: Relevance
“…; Tomsett et al . ). These studies showed, for example, that the lower frequencies of the synaptic input current give the largest contributions to the LFP for two reasons.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Tomsett et al . ). These studies showed, for example, that the lower frequencies of the synaptic input current give the largest contributions to the LFP for two reasons.…”
Section: Introductionmentioning
confidence: 97%
“…; Tomsett et al . ), recent studies have also been done with neuron models with active dendrites (Schomburg et al . ; Reimann et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we shall broadly distinguish two levels that are relevant to the characterization of stimulus effects: (i) the neuronal description level, where the (firing and sometimes dendritic) activity of single neurons are modeled; and (ii) the population description level, where the activity of an entire neural population is described, often by population average variables. Figure 1 illustrates examples of these two approaches on simulating a cortical patch of tissue in two recently developed models (Tomsett et al, 2015;Wang et al, 2014). There are several books and reviews on either approach and on the relationship between the two (Coombes, 2006;Deco et al, 2008;Gerstner and Kistler, 2002).…”
Section: Modeling Of Stimulation Modalitiesmentioning
confidence: 99%
“…Numbers on the right indicate cortical depth in micrometers. See Tomsett et al (2015) and www.vertexsimulator.org for details. Bottom: Population-level description, where average excitatory and inhibitory population firing dynamics are simulated.…”
Section: Modeling Of Stimulation Modalitiesmentioning
confidence: 99%